2010
DOI: 10.1155/2010/835984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Juvenile Idiopathic Arthritis on Kinematics and Kinetics of the Lower Extremities Call for Consequences in Physical Activities Recommendations

Abstract: Juvenile idiopathic arthritis (JIA) patients (n = 36) with symmetrical polyarticular joint involvement of the lower extremities and healthy controls (n = 20) were compared concerning differences in kinematic, kinetic, and spatio-temporal parameters with 3D gait analysis. The aims of this study were to quantify the differences in gait between JIA patients and healthy controls and to provide data for more detailed sport activities recommendations. JIA-patients showed reduced walking speed and step length, strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
2
22
1
12
Order By: Relevance
“…Differences in EE and accelerometer counts could be attributed to factors related to disease pathophysiology, sequelae, and drug treatment (42,43). For example, mechanical efficiency due to joint damage or contractures or muscle atrophy from medication and muscle disuse in JA or JDM (23,42); decreased lung function in CF (36) and disturbed muscle metabolism in IMD as well as deconditioning or poor neuromotor control may explain the differences in patterns of movement and increased energy cost of performing physical activities (8,24). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in EE and accelerometer counts could be attributed to factors related to disease pathophysiology, sequelae, and drug treatment (42,43). For example, mechanical efficiency due to joint damage or contractures or muscle atrophy from medication and muscle disuse in JA or JDM (23,42); decreased lung function in CF (36) and disturbed muscle metabolism in IMD as well as deconditioning or poor neuromotor control may explain the differences in patterns of movement and increased energy cost of performing physical activities (8,24). …”
Section: Discussionmentioning
confidence: 99%
“…Children with disease often have inherent physiological or biomechanical differences from healthy children (gait deficiencies or metabolic abnormalities) that require them to work at a higher energy level to complete the same task (16,18,22,36). For example, a recent gait analysis study of 36 children diagnosed with polyarticular arthritis revealed significant differences in walking mechanics including: slower walking speeds, a shorter stride length, reduced hip and knee extension, tilted pelvis and improper foot mechanics when compared to healthy controls (23). These changes may lead to a higher energy cost of locomotion; such differences may not be accounted for by the currently available prediction equations and cut-point estimates and could produce significant bias in determining energy expenditure or activity levels if used in their current form.…”
Section: Introductionmentioning
confidence: 99%
“…), результаты которого были опубликованы в 2010 г. [34]. В этой клинике был раз-работан метод 3D-анализа походки.…”
Section: T Takken и соавтunclassified
“…B. Nordic Walking oder Klettern, sind zu bevorzugen. Höhere Impulskräfte wie Stoppen, Stoßen oder Schlagen sollten noch vermieden werden [2,12,14].…”
Section: Sporttherapieunclassified
“…Die funktionelle Behandlung jenseits medikamentöser Therapien muss daher in Zukunft wieder mehr in den Blickpunkt rücken. Neben der klassischen Physio-und Ergotherapie wurden in den letzten Jahren auch medizinische Trainingstherapien für rheumakranke Kinder und Jugendliche auf Basis sportwissenschaftlicher Analysen entwickelt [2]. Damit gehört das generelle Sportverbot für Rheumakinder der Vergangenheit an.…”
unclassified